Barriers to Using Computers in Education - O. Iskrenovic-Momchilovic (University of Sofia, 2020)
This paper discusses the barriers that prevent the use of computers in teaching, as well as the possibilities of their elimination in order to achieve precise acquisition of knowledge in various fields. The survey considered five research questions and answers using mean and standard deviation. Two hypotheses were formulated and tested using the z-test statistical tool. The results show that students believe that using computers in teaching limited and that the most important barrier is technical equipment in the educational institution. All barriers can be overcome by organizing a large number of useful and practical courses and seminars about computers. The results have confirmed that there are no significant differences between male and female students in thinking about the barriers to using computers in teaching.